Optimizing basketball player performance through zig-zag run training: Impact on speed and agility - Gilang Permana Putra; Himawan Wismanadi; Roy Januardi Irawan; Hijirin Fithroni (Universitas Sriwijaya, 2026)
Research Problems: Basketball requires good speed and agility to support movement and quick direction changes. However, many school-level athletes do not yet have specific training programs to improve these abilities. Research Objectives: This study aims to examine the effect of zig-zag run training on speed and agility in basketball players. Methods: This study used a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 15 students participating in basketball extracurricular activities. The training program was conducted for six weeks. The instruments used were the Illinois Agility Test and the 30-meter sprint test. Results: Agility improved from 9.01 seconds to 8.41 seconds, and 30-meter sprint time improved from 7.67 seconds to 5.98 seconds. Statistical analysis showed a significant difference (p < 0.05). Conclusion: Zig-zag run training is effective in improving speed and agility and can be used as an alternative training method for school-level basketball athletes.